Memórias do Tocantins no livro O Primeiro Picolé, de José Francisco Concesso - Silva, Madaire Gomes (Universidade Federal do Tocantins, 2020)
This monograph had as main objective to analyze the presence of the memory and the regional experience in the work "My First Popsicle" (2004) of the writer from Minas Gerais, who lived in Tocantins since the 1980s, José Francisco da Silva Concesso. We aim to draw a relation of memory in the literature assigning to the exercise of memory the construction of images about the region's past. The act of remembering is valuable to literature, for in it we expose our identity that is recovered by remembering to make the identity in writing visible. The research has a bibliographical approach, addressing the themes of memory, of the biography of the author, selecting as corpus the texts that compose the collection that more closely take as space for the narrative the city of Araguaína and / or its surroundings. As a theoretical basis to subsidize the analyzes, we mobilize the discursive semiotics, privileging in the cut the dimension of the figurativeness. As we intend to show, the texts dealing with a past time, often inaccurate from the point of view of the dates evoked, constituted as a "time of the time", bring images of precariousness, abandonment, ignorance, presupposing an enunciator destinador that evaluates , through his position as a migrant newcomer to the place, from a dysphoric perspective. At the same time, this gaze on the past beckons for its overcoming, in the present of writing, when the past there figurativized is overcome by the transformations in urban space and local culture.